Black Men's Health A Strengths-Based Approach Through a Social Justice Lens for Helping Professions - Dyson, Yarneccia D.; Robinson-Dooley, Vanessa; Watson, Jerry (Cham : Springer International Publishing : Imprint: Springer, 2022)
Now more than ever there is a need to focus on Black men's health in higher education and ensure that future practitioners are trained to ethically and culturally serve this historically oppressed community. This textbook provides practical insight and knowledge that prepare students to work with Black men and their families from a strengths-based and social justice lens. There is a dearth in the literature that discusses the prioritization of Black men's health within the context of how they are viewed by societal approaches to engage them in research, and health programming aimed at increasing their participation in health services to decrease their morbidity and mortality rates. Much of the extant literature is over 10 years old and doesn't account for social determinants of health, perceptions of health status, as well as social justice implications that can affect the health outcomes of this historically oppressed population including structural and systemic racism as well as police brutality and gun violence. The book's 13 chapters represent a diversity of thought and perspectives of experts reflective of various disciplines and are organized in four sections: Part I - Racial Disparities and Black Men Part II - Black Masculinity Part III - Black Men in Research Part IV - Social Justice Implications for Black Men's Health Black Men's Health serves as a core text across multiple disciplines and can be utilized in undergraduate- and graduate-level curriculums. It equips students and educators in social work, nursing, public health, and other helping professions with the knowledge and insight that can be helpful in their future experiences of working with Black men or men from other marginalized racial/ethnic groups and their families/social support systems. Scholars, practitioners, and academics in these disciplines, as well as community-based organizations who provide services to Black men and their families, state agencies, and evaluation firms with shared interests also would find this a useful resource.
Part I. Racial Disparities and Black Men -- Chapter 1. Modern Epidemiological Impacts on Black Men's Health: Using a Social Justice-Oriented Analysis -- Chapter 2. Black Men and Healthy Together: Self-Management of Chronic Disease and Behavioral Health -- Chapter 3. Positionality and Unpacking Current Perspectives on Black Male Health Towards Transformative Action -- Part II. Black Masculinity -- Chapter 4. Beyond Moving the Ball in Youth Sports: Making the Case for Mental Health for Black Youth -- Chapter 5. The Psychological Colonization of Black Masculinity: Decolonizing Mainstream Psychology for White Allies Working in Mental Health with Black Men -- Chapter 6. Black Masculinity Remixed -- Chapter 7. Building a Movement with Black Men: Culture Is the Key -- Part III. Black Men in Research -- Chapter 8. Asserting Voice: Navigating Service Delivery and Community Resources -- Chapter 9. "The Talk" Revisited: Expanding the Conversation with Black Males in Trauma -- Chapter 10. Innovative Strategies to Engage Black Men in Research -- Part IV - Social Justice Implications for Black Men's Health - Chapter 11. Social Justice and Black Men's Health -- Chapter 12. Advocacy, Politics, and the Sporting World's Response to Racial Unrest -- Chapter 13. Social Justice Implications for Black Men's Health: Policing Black Bodies.
Keywords: Social work education; Health; Sex; Race; Social justice; Psychology; Men; Social Work Education; Gender and Health; Race and Ethnicity Studies; Social Justice; Behavioral Sciences and Psychology; Mens' Studies